Highly Efficient Catalytic Oxidative Desulfurization of Dibenzothiophene using Layered Double Hydroxide Modified Polyoxometalate Catalyst - Nur Ahmad; Muhammad Badaruddin; Nova Yuliasari; Fitri Suryani Arsyad; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Layered double hydroxide-modified polyoxometalate (ZnAl-PW) was prepared and used for the oxidative desulfurization of dibenzothiophene. XRD patterns of ZnAl-LDH and PW are still present in ZnAl-PW. The bands of ZnAl-PW in wavenumber 3276, 1637, 1363, 1050, 952, 887, and 667 cm-1. The typical surface of ZnAl-LDH and ZnAl-PW can be observed not smooth in different sized with irregular shapes. The average diameter distribution of ZnAl-LDH and ZnAl-PW is 14 nm and 47 nm, respectively. For dibenzothiophene with 500 ppm, conversion on ZnAl-LDH, PW, and ZnAl-PW was 94.71%, 95.88%, and 99.16%, respectively. Conversion of dibenzothiophene in line with the acidity of ZnAl-LDH, PW, and ZnAl-PW were 0.399, 1.635, and 3.023 mmol/gram, respectively. The most effective catalyst dosage for the desulfurization of dibenzothiophene on ZnAl-LDH, PW, and ZnAl-PW is 0.25 g. The unchanged dibenzothiophene concentration indicates a heterogeneous system. ZnAl-LDH, PW, and ZnAl-PW are truly heterogeneous catalysts. After 3 cycles of oxidative desulfurization, the percentage conversion of dibenzothiophene on ZnAl-LDH, PW, and ZnAl-PW were 77.42 %, 65.98%, and 86.38%, respectively. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).